Review–From LiMn2O4 to Partially-Disordered Li2MnNiO4: The Evolution of Lithiated-Spinel Cathodes for Li-Ion Batteries. Issue 2 (1st February 2022) - Thackeray, Michael M.; Lee, Eungje; Shi, Boyu; Croy, Jason R.
Abstract : This personal narrative relates to the discovery in 1981 of stoichiometric LiM2 O4 spinel electrodes (where M = metal cation) for lithium-ion batteries by the Goodenough group at Oxford University, UK, and the subsequent identification and evolution of stable lithiated-spinel Li2 M2 O4 (or LiMO2 ) cathodes at the Council for Scientific and Industrial Research in South Africa and Argonne National Laboratory (USA). The competition that occurs between the formation of lithiated-spinel and layered (LiMO2 ) structures at 400 °C, and recent efforts to design high-capacity, Mn-rich composite cathodes with partial disorder, are discussed. The paper is written in honor of John Goodenough's 100th birthday.